FABRICATION AND ELECTROCHEMICAL EVALUATION OF THE LITHIUM BATTERY, Li0.5La0.5TiO3/LiFePO4-C INTERFACE - K. P. Abhilash; P. Christopher Selvin; B. Nalini; M. V. Reddy (Pattimura Proceeding, 2017)
The Li0.5La0.5TiO3 and LiFePO4/C has been prepared using sol-gel method for its interface analysis towards its application for all solid state assembly. The LiFePO4cathode material and Li0.5La0.5TiO3 solid electrolyte has been individually tested for its electrochemical reversibility. The thin film battery assembly shows severe capacity fading, which results in electrochemically non active with the chosen anode materials. In order to verify the electrochemical activity and interaction of Li0.5La0.5TiO3-LiFePO4/C interface the mixture has been tested for its electrochemical reversibility. The Li0.5La0.5TiO3-LiFePO4/C interface exhibits well resolved oxidation-reduction hype which verifies its suitability towards all solid state assemblies.